2016
DOI: 10.18006/2015.4(1).59.65
|View full text |Cite
|
Sign up to set email alerts
|

Wild edible mushrooms of Nagaland, India: a potential food resource

Abstract: Wild edible mushrooms (WEM) are known for its medicinal and nutritional value across the globe. WEM have become one of the most prized after food especially in the developed countries where people are mostly health conscious. The present study throws light on the diverse flora of WEMs of Nagaland and how it can be income generator for the tribal people with proper research in this aspect. Till now, the knowledge of distinguishing between edible and non-edible varieties is only confined to people who go for mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…The local and tribal peoples identify wild mushrooms based on their own perception, knowledge and phenological characters and the naming of the species is done in local dialect to keep memory and transfer the knowledge from one generation to the next. Such observations were also reported by many workers [25,26]. Out of 20 wild edible mushroom species 15 species were documented from the forest soil substratum during the rainy seasons.…”
Section: Diversity Indicessupporting
confidence: 67%
“…The local and tribal peoples identify wild mushrooms based on their own perception, knowledge and phenological characters and the naming of the species is done in local dialect to keep memory and transfer the knowledge from one generation to the next. Such observations were also reported by many workers [25,26]. Out of 20 wild edible mushroom species 15 species were documented from the forest soil substratum during the rainy seasons.…”
Section: Diversity Indicessupporting
confidence: 67%
“…The L. piperatus (L.) Pers. is an edible mushroom belong to Russulaceae found in sub-tropical semievergreen forests (23). In the present study this wood inhabiting fungi was found to be growing on decomposing leafy litter soil of Kondapalli forest.…”
Section: Collection Examinedsupporting
confidence: 50%
“…In Nagaland, WEMs are considered as traditionally important nutritious food which forms a vital part of the food culture of all the ethnic tribes. Recently, it is reported that Nagaland is home for 37 WEM species and the number is likely to increase as study progresses (Ao et al 2016). In this study, the local markets were surveyed to gather information on the wild edible varieties consumed by the locals.…”
Section: Introductionmentioning
confidence: 99%